Changes in the lower limb alignment during the gait in advanced phases of pregnancy and the effect of special footwear - M. Gimunová; M. Zvonař; P. Šagat; I. Duvač (Universidad de Murcia, 2018)
The hip, knee and foot pain are common complaints during pregnancy as pregnancy affects the musculoskeletal health. The purpose of the study was to investigate the pregnancy gait adaptations and the effect of special footwear. 16 pregnant women divided into a control and experimental group, who obtained the special footwear, participating at 27, 32 and 37 gestational weeks in data collection sessions. At each session participants were asked to go barefoot in a space captured by the Simi Motion®. To compare the differences between different collection sessions, effect size obtained by Cohen's d was used. Results of this study showed, that using the tested footwear enabled a verticalization of the pelvic segment, increase of the maximum hip extension angle, reduction of foot-floor angle and maintaining the same height of the knee during walking in the experimental group, possibly decreasing the risk of pain development in these body segments during pregnancy.